Exploring the Difficulties of Speaking English Encountered by Senior High School Students - Natalia Delina (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was conducted to investigate the difficulties experienced by the tenth-grade students in speaking English at one of the senior high schools in Jember in the 2023/2024 academic year. The participants in the research were the tenth-grade students. The participants of this study were selected with the help of the tenth-grate English teacher in one of the senior high schools in Jember. The researcher asked the teacher to help choose ten students by determining the average score in English subjects, especially in speaking. Based on data analysis regarding the difficulties experienced by students in speaking English, five students said that students often look for the right words to put together into a sentence and then say them. This case occurred with a student who said he had difficulty determining the right words to use in English conversations correctly. Three students said that their vocabulary mastery still needs to be improved, making it difficult for them to determine the right words so that they can be arranged into the correct sentence. Seven students experience difficulties due to a lack of understanding of grammar, such as learning verbs, adjectives, and conjunctions. Three students experienced difficulties due to poor pronunciation. Four students said another difficulty was needing friends with whom they could communicate intensively using English. Other difficulties experienced by students are related to their psychology, such as lack of self-confidence, shyness, and nervousness, especially when practicing speaking in front of the class or making presentations. Based on data analysis, the researcher can conclude that the difficulties experienced by high school students in speaking English consist of three factors namely: First, the knowledge factor is related to the difficulties in learning and understanding basic knowledge in speaking English, including vocabulary, pronunciation, grammar, fluency, and comprehension. These difficulties include the inability to select the appropriate vocabulary, a lack of mastery of the language, grammatical errors, and a lack of clarity in pronunciation. Second, environmental factors are related to the surrounding conditions that can support whether or not a person (student) learns and practices speaking English. This difficulty is a need for friends to communicate with intensity. Third, psychological factors related to difficulties originating from students' feelings, emotions, and thoughts include a lack of self-confidence, embarrassment, nervousness, or anxiety. Therefore, the researcher would like to give some suggestions for the school's need to provide an interesting English learning system so that students can easily understand the material. Teachers should provide training more often in the form of practical dialogue with classmates or dialogue with teachers so that students are trained, brave, and confident. Parents who can speak English should accompany their children to learn to speak English so that they become familiar with and fluent. Parents can also help their children look for information on YouTube channels or social media that can support their children in learning to speak English. Students must know themselves to know what type of learning method they prefer.
Reupload File Repositori 24 Februari 2026_Teddy/Hendra
Keywords: EXPLORING; DIFFICULTIES; ENCOUNTERED